Canine brain tumours: a model for the human disease?. (18th May 2015) - Hicks, J.; Platt, S.; Kent, M.; Haley, A.
Abstract: Canine brain tumours are becoming established as naturally occurring models of disease to advance diagnostic and therapeutic understanding successfully. The size and structure of the dog's brain, histopathology and molecular characteristics of canine brain tumours, as well as the presence of an intact immune system, all support the potential success of this model. The limited success of current therapeutic regimens such as surgery and radiation for dogs with intracranial tumours means that there can be tremendous mutual benefit from collaboration with our human counterparts resulting in the development of new treatments. The similarities and differences between the canine and human diseases are described in this article, emphasizing both the importance and limitations of canines in brain tumour research. Recent clinical veterinary therapeutic trials are also described to demonstrate the areas of research in which canines have already been utilized and to highlight the important potential benefits of translational research to companion dogs.